The Question of Provenance and the Economics of Deuteronomy - Richter, Sandra L. (Journal for the study of the Old Testament, 2017)
The age-old question of the social location(s) of the book of Deuteronomy remains critical to the academic discussion of the book. The thesis of this article is that the culturally embedded economic realities of Urdeuteronomium (forthrightly addressed as an element of narrative or law, alluded to via metaphor or backdrop, or even mistakenly included as anachronism) should have something to teach us regarding the provenance of the book. Toward this end, this article surveys the archaeologically reconstructed picture of the economies of the Iron I, IIA, B, and C in ancient Israel, identifying diagnostic features of each in rural and urban areas, juxtaposes those features to the contents of Urdeuteronomium, and asks what may be discerned of the social setting of the book.